Esfera pública virtual : Una lectura política y comunicacional de lo público en la web - Vázquez, Mariano Darío (2018)
This work explores the theoretical development of the virtual public sphere (EPV, as per its Spanish acronym). To respond to it, the article focuses mainly on: the genesis of the public sphere, the publications in social networks and the biographical suture, the double status of the public sphere, the tension between value in use and value in exchange, the virtual aspects of the EPV, and a brief appendix on trolls and post-truth. The EPV is an approach to interactions on the web that was developed within the framework of a PhD thesis, to study the demonstrations against the open-air mega-mining project promoted by the government of the province of La Rioja and the company Canadian Osisko Mining Corporation. This research uses the case study “Do not touch The Famatina” to review the construction of EPV.